2020
DOI: 10.1007/s00414-020-02407-9
|View full text |Cite
|
Sign up to set email alerts
|

The recovery of touch DNA from RDX-C4 evidences

Abstract: RDX (Royal Demolition Explosive) is the organic compound with the formula (O2NNCH2)3. It is a white solid material without smell or taste, widely used as an explosive. It is more energetic explosive than TNT, and it was used widely in World War II. The estimated number of RDX-C4 cases in Bahrain ranged between the years 2015-2018 (May) with a total quantity of 370.72 KG in a total number of 38 cases. The effect of explosive RDX-C4 is very massive and can cause many causalities and fatalities among civilians an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…According to a previous study utilizing DNA touch techniques, DNA quantities in areas close to an explosion, specifically inside the bag, were lower than those in areas more distant from the blast, such as the bag's handle. 20 Previous studies have identified suicide bombers through DNA using sweat and saliva samples, with DNA typing and matching rates of 12% and 48%, respectively. 21 Additionally, a study in 2012 investigating DNA touch samples on a backpack showed contamination of alleles from other individuals (50.9%) and the absence of any detectable alleles (4.7%).…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study utilizing DNA touch techniques, DNA quantities in areas close to an explosion, specifically inside the bag, were lower than those in areas more distant from the blast, such as the bag's handle. 20 Previous studies have identified suicide bombers through DNA using sweat and saliva samples, with DNA typing and matching rates of 12% and 48%, respectively. 21 Additionally, a study in 2012 investigating DNA touch samples on a backpack showed contamination of alleles from other individuals (50.9%) and the absence of any detectable alleles (4.7%).…”
Section: Discussionmentioning
confidence: 99%